Feedback in augmented and virtual reality piano tutoring systems: a mini review - Wilson, Katie; Pfeiffer, Phillip E. (Frontiers in Virtual Reality, 2023)
Researchers in music education are exploring the use of virtual reality (VR) and augmented reality (AR) to support piano instruction. Beginner piano students tend to receive short, infrequent lessons, which they practice on their own. This lack of instructor feedback creates opportunities for students to develop improper technique. Current strategies for using AR and VR to guide solo practice use moving shapes to help students to identify what notes to play. Improvements in commercial AR/VR technology will be needed to provide more detailed real-time feedback.